1993
DOI: 10.1213/00000539-199301000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Produces Endothelium-Independent Vasodilation and May Act as a Ca2+Channel Blocker

Abstract: The mechanism of vasodilation induced by propofol was investigated using isolated rat thoracic aortic rings. Aortic rings were precontracted with potassium chloride (KCl) (40 mM) or phenylephrine (PE) (3 x 10(-8) to 3 x 10(-7) M) in the presence and absence of intact endothelium. Propofol produced similar concentration-dependent relaxation in aortic rings with and without endothelium regardless of whether they were precontracted with KCl or PE. The relaxation response to propofol was significantly greater in K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(46 citation statements)
references
References 0 publications
3
41
0
2
Order By: Relevance
“…20 It has been shown that propofol can decrease Ca 2þ influx in smooth muscle through either voltage-gated Ca 2þ channels or/and receptor-mediated channels, depending on which is predominantly present. 15,16 In the present study, preincubation of aorta with propofol suppressed both the initial and the sustained contraction to NE. However, propofol only suppressed the slow and sustained, but not the fast initial, contractions in aorta from LPS-treated rats.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…20 It has been shown that propofol can decrease Ca 2þ influx in smooth muscle through either voltage-gated Ca 2þ channels or/and receptor-mediated channels, depending on which is predominantly present. 15,16 In the present study, preincubation of aorta with propofol suppressed both the initial and the sustained contraction to NE. However, propofol only suppressed the slow and sustained, but not the fast initial, contractions in aorta from LPS-treated rats.…”
Section: Discussionsupporting
confidence: 55%
“…11,12,14 By contrast, vasodilation in response to propofol has been attributed to a decrease in intracellular Ca 2þ availability within vascular smooth muscle cells, reflecting inhibition of the Ca 2þ influx through voltage-or receptor-gated Ca 2þ channels. 12,15,16 Propofol is widely used not only in anesthesia but also in critical care units. 17 Therefore, whether arterial sensitivity to vasoconstrictors and/or vasodilators can be modulated by propofol is an important issue in ill patients.In this study, we investigated the effect of propofol on norepinephrine (NE)-induced contractile responses in thoracic aortas isolated from Wistar rats treated with LPS.…”
Section: Introductionmentioning
confidence: 99%
“…Vasoconstriction induced by increases in intracellular calcium is triggered by one of two mechanisms: influx of calcium through the sarcolemma and mobilization of calcium from intracellular stores. 22 Propofol has been demonstrated to induce vasodilatation by inhibition of calcium mobilization induced by phenylephrine and norepinephrine, which has been studied in the rat aorta 23 and rabbit mesenteric resistance vessels; 24 and propofol to inhibits calcium influx through L-type Ca 2+ channels induced by endothelin-1 in rat aortic smooth muscle. 25 This effect of propofol has also been shown and to inhibit calcium influx induced by norepinephrine in rabbit mesenteric resistance vessels, 24 rat aorta, 23 and porcine coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…22 Propofol has been demonstrated to induce vasodilatation by inhibition of calcium mobilization induced by phenylephrine and norepinephrine, which has been studied in the rat aorta 23 and rabbit mesenteric resistance vessels; 24 and propofol to inhibits calcium influx through L-type Ca 2+ channels induced by endothelin-1 in rat aortic smooth muscle. 25 This effect of propofol has also been shown and to inhibit calcium influx induced by norepinephrine in rabbit mesenteric resistance vessels, 24 rat aorta, 23 and porcine coronary arteries. 26 In addition to a calcium blocking action, propofol may also relax smooth muscle by activation of Ca 2+ -dependent K + channels as demonstrated in human umbilical vessels.…”
Section: Discussionmentioning
confidence: 99%
“…mediated decrease in sympathetic activity may explain all the hemodynamic changes 10,11 although direct vascular smooth muscle relaxation 14 and direct negative inotropic 13,15 effect may contribute to a lesser extent. This decrease in blood pressure may not be clinically significant in young and healthy individuals, but significant hypotension during induction has been reported to correlate with longer post operative stay 6 .…”
mentioning
confidence: 99%